Frequency of hepatitis B and C in health care providers at three referral hospitals in Libya - Abdel-Naser Elzouki; Rafat Lubbad; Islam Elzouki; Ahmed Elhaddad; Abdulfattah Ibrahim (The Pan African Medical Journal, 2020)

(untitled)
INTRODUCTION: The aim of the present study was to determine the frequency of HBsAg and anti-HCV antibodies in health care providers (HCPs) at three referral hospitals in Libya, and to correlate the HBsAg status with history of hepatitis B vaccination among HCPs. METHODS: one hundred eighty-two HCPs, with a mean age (±SD) of 32.9±8 years and age range from 20 to 59 years, were enrolled in this study. They were 50 doctors, 68 nurses, 42 laboratory technicians, 12 hospital cleaners, five anesthesia technicians and five midwives. They were tested, after obtained a written consent, for the presence of HBsAg and Anti-HCV antibodies by enzyme linked immuno-sorbent assay (ELISA) techniques. A pre-test questionnaire was filled by each HCP to verify place of work, working period, type of work, status of HBV vaccination, and history of needle stick injury. RESULTS: four HCPs have Anti-HCV antibodies positive (2.2%) and nine were HBsAg positive (4.9%). Only 52% (95/182) of the HCPs received full dose of hepatitis B vaccine, while the others either not completed the vaccination schedule or have not receive it. One hundred (54.9%) of the participants had exposed to blood via needle stick injury during their work, 6 (6%) of them were HBsAg positive and three (3%) were anti-HCV positive. Needle stick injury was considered as primary risk factor in 66.7% (6/9 HCPs) of HBsAg-positives and 75% (3/4 subjects) of anti-HCV-positives. CONCLUSION: the present study showed a higher frequency of HBsAg than anti-HCV among HCPs in three major hospitals in Libya. This difference may be explained by the low hepatitis B vaccination rate and the high rate of needle stick injury among this high risk group for these infections.